The impact of the merger goodwill on the profitability of the enterprise. Issue 4 (3rd July 2016) - Xiao, Li; Liu, Yiwei
Abstract: In this paper, 2008–2012 listed in Shanghai and Shenzhen information industry companies as samples, empirical information industry listed companies merger affect the goodwill of corporate profitability. The study found that the information industry listed companies in general goodwill positively correlated with profitability, and the greater the proportion of goodwill, to bring the stronger profitability. The research results provide reference information industry, listed companies in the merger process, whether the acquisition premium.